Improving access to cancer care among rural populations in India: Development of a validated tool for health system capacity assessment - Meritxell Mallafré‐Larrosa; Arunah Chandran; Kunal Oswal; Ishu Kataria; Arnie Purushotham; Rengaswamy Sankaranarayanan; Rajaraman Swaminathan; Rohit Rebello; Rita Isaac; Moni Kuriakose; Richard Sullivan; Partha Basu; et al. (Cancer Medicine)
Abstract Background Cancer burden in India is rapidly growing, with oral, breast, and uterine cervix being the three most commonly affected sites. It has a catastrophic epidemiological and financial impact on rural communities, the vast majority of whom are socio‐economically disadvantaged. Strengthening the health system is necessary to address challenges in the access and provision of cancer services, thus improving outcomes among vulnerable populations. Objective To develop, test, and validate a health system capacity assessment (HSCA) tool that evaluates the capacity and readiness for cancer services provision in rural India. Methods A multi‐method process was pursued to develop a cancer‐specific HSCA tool. Firstly, item generation entailed both a nominal group technique (to identify the health system dimensions to capture) and a rapid review of published and gray literature (to generate items within each of the selected dimensions). Secondly, tool development included the pre‐testing of questionnaires through healthcare facility visits, and item reduction through a series of in‐depth interviews (IDIs) with key local stakeholders. Thirdly, tool validation was performed through expert consensus. Results A three‐step HSCA multi‐method tool was developed comprising: (a) desk review template, investigating policies and protocols at the state level, (b) facility assessment protocol and checklist, catering to the Indian public healthcare system, and (c) IDI topic guide, targeting policymakers, healthcare workforce, and other relevant stakeholders. Conclusions The resulting HSCA tool assesses health system capacity, thus contributing to the planning and implementation of context‐appropriate, sustainable, equity‐focused, and integrated early detection interventions for cancer control, especially toward vulnerable populations in rural India and other low‐resource settings.